Energy Efficient Frame Structure for Gigabit Passive Optical Networks - Rizwan Aslam Butt; Sevia Mahdaliza Idrus; Raja Zahilah Radzi; Kashif Naseer Qureshi (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Increasing power consumption in information and communication access networks is one of the major cause of greenhouse gas emissions. These emissions are harmful to life on earth. Passive Optical Networks (PONs) are energy efficient but the broadcast nature of downstream traffic may cause of huge unnecessary processing of frames by the optical network units and result in significant energy wastage. Bi-PON technique tried to solve this problem by changing the XGPON / GPON frame structure to an interleaved pattern but also required additional hardware changings at the optical network units.  In this study, we have tried to achieve the same objective by making a few changings in the GPON frame structure without modifying the existing hardware structure. The simulation results show that 25.25% processing energy of an ONU can be saved by incorporating these changes.